Cardiovascular risk estimation and management in rheumatoid arthritis: Comment on the EULAR evidence-based recommend-ations for cardiovascular risk management in patients with rheumatoid arthritis - (:unkn) unknown (Clinical and Experimental Rheumatology S.A.S., 2014)
[No abstract available]